BaCl2 an efficient replacement of CdCl2 treatment step for thermally deposited CdTe thin film. (22nd May 2019) - Syed, Waqar A A; Ali, Ahsan; Rafiq, Nouman; Shah, Wiqar H; Shah, Nazar A; Yasir, Muhammad
Abstract: Cadmium telluride (CdTe), a II–VI compound semiconductor has long been identified as suitable absorber material. A central part of the fabrication process includes the coating of cadmium chloride on CdTe thin films. Coating of CdCl2 has severe disadvantages; it is expensive and a water-soluble source of toxic cadmium ions, making it extremely environment unfriendly. We report the development of barium chloride (BaCl2 ) as an efficient coating material for CdTe thin film. We have demonstrated that CdTe thin films can be prepared using BaCl2 which is non-toxic and costs effective and may replace CdCl2 . Coating of BaCl2 helps distribution of acceptor like impurities resulting in p-conversion of the cadmium telluride layer. The structural, electrical and optical properties of BaCl2 coated CdTe thin films have been investigated and results are presented.